IPENERAPANiMODELiPEMBELAJARANiKOOPERATIFiTIPEiTWOIiSTAYiTWOiSTRAYiTERHADAP KEMAMPUANiPEMAHAMAN IKONSEPiMATEMATISiPESERTAiDIDIK KELASiXI MIPA SMAN 1I GUNUNG TULEH - Gusmalia Gusmalia (Jurnal Edukasi dan Penelitian Matematika, 2022)
One of the objectives of learning mathematics is that students have a good understanding of mathematical concepts. However, students' conceptual understanding is still relatively low. One of the efforts that can be done to improve students' understanding of mathematical concepts is to apply the Two Stay Two Stray type of Cooperative learning model. students who study with conventional learning and describe the development of students' understanding of mathematical concepts during the implementation of the Two Stay Two Stray Cooperative learning model in class XI MIPA SMA Negeri 1 Gunung Tuleh. This type of research is a quasi-experimental with the nonequivalent posttest-only control group design. The population of the study was students of class XI MIPA SMA Negeri 1 Gunung TulehT for the academic year 2022/2023 with class XI MIPA 1 as the experimental class and XI MIPA 2 as the control class. Research data were collected through quizzes and tests of students' mathematical concept understanding abilities. Quiz score data were analyzed based on the average score, as well as the percentage of students' scores per indicator. The test data were analyzed using t-test.  Based on the results of data analysis, it can be concluded that in general the development of students' understanding of mathematical concepts has increased while using the TSTS model. Then, based on the results of hypothesis testing, it can be seen that the understanding of mathematical concepts of students who use the TSTS learning model is better than the understanding of mathematical concepts of students who study with conventional learning models. So it can be concluded that there is an influence of the TSTS learning model on the understanding of students' mathematical concepts. Keywords– TSTS learning model, Mathematical Concepts Understanding,Quasi Experiment